The acquisition of finiteness - Blom, Elma, 1972- (Studies in generative grammar, 2008)
The book provides a theoretical and empirical evaluation of a field that has been the focus of generative theories on language acquisition: the acquisition of finiteness and related properties such as root infinitives, verb movement and null subjects. It contains a critical empirical assessment of the various hypotheses, lists the implications for linguistic theory and provides alternative analyses. Issues covered are: (i) the semantics of children's root infinitives (tense, modality and aspect), (ii) the relation between lexical, morphological and syntactic development in the domain of finite.